Polymerized 4-Fold Coordinated Carbonate Melts in the Deep Mantle - Sanloup, Chrystèle; Hudspeth, Jessica M.; Afonina, Veronika; Cochain, Benjamin; Konôpková, Zuzana; Lelong, Gérald; Cormier, Laurent; Cavallari, Chiara (Frontiers in Earth Science, 2019)
Our understanding of the deep carbon cycle has witnessed amazing advances in the last decade, including the discovery of tetrahedrally coordinated high pressure (P) carbonate phases. However, little is known on the properties of molten carbonates at depth, while their properties at lower mantle conditions are unknown. Here, we report the structure and density of FeCO3 melts and glasses from 44 GPa to 110 GPa by means of in situ x-ray synchrotron diffraction, and ex situ Raman and x-ray Raman spectroscopies. Carbon is fully transformed to 4-fold coordination, a bond change recoverable at ambient P. While low P melts react with silica, resulting in the formation of silico-carbonate glasses, high P melts are not contaminated but still quench as glasses. Carbonate melts are therefore polymerized, highly viscous and poorly reacting with silicates in the lower mantle, in stark opposition with their low P properties.